A stable hydrazine click fluorescent probe based on photo switch. (February 2021) - Guan, Pengli; Yang, Binsheng; Chai, Jie; Wen, Guangming; liu, Bin
Abstract: One novel aggregation induced emission (AIE) fluorescent probe for hydrazine (N2 H4 ) (T ) was synthesized. This is an optically controlled process. The probe is very stable before light, which is different from many probes with ester bonds that are easily hydrolyzed during storage. Only under ultraviolet (UV) light irradiation, T responded to N2 H4 rapidly in aqueous solution along with the fluorescence change from yellow to blue. The detection limit is as low as 0.25 μM, and it works well at a wide pH range (3–10) in aqueous solutions. Bio-imaging of N2 H4 in living cell demonstrated a favorable biocompatibility. Moreover, the optically controlled mechanism was exploited. The result indicated that the Schiff base structure of T would be twisted under UV light irradiation, which loosened the original aggregation state. Consequently, T became more accessible to N2 H4 . That is, aggregation state of T is inactive, only in the presence of UV light the reactivity could be activated. Interestingly, the torsion of this compound can be restored by visible light irradiation or heating. This is the first report about optically controlled AIE fluorescent probe. Graphical abstract: Image 1 Highlights: A UV light dependent fluorescence probe could respond quickly to N2 H4 . The probe is stable and works well at a wide pH range from 3 to 10 in aqueous solutions. Bio-imaging of N2 H4 in living cell demonstrated a favorable biocompatibility.